Control de plagas con tres biorepelentes en el cultivo del maíz (Zea Mays L.) hibrido 551 y ag 003 en la zona de Quevedo. - López Carpio, Oscar Stalin (2013)
The present research was conducted at the Experimental Farm "La Maria", owned by the State Technical University Quevedo, located at Km 7 Track Quevedo-The Junction, a trial was corn entitled "Pest Control with three biorepelentes in maize (Zea mays L.) Hybrids AG Iniap H 551 and 003 in the Quevedo assessed the response of maize to the application of various based biorepelentes some plant extracts, in order to evaluate the dose effects of products on the agronomic performance of corn; evaluate appropriate dose products. Experimental design was used randomized complete blocks with three replications and ten treatments. The experimental plot had an area of 19.0 m2, while the usable area of the plot was determined by the two central rows, giving an area of 9.0 m2. Variables were evaluated: days to male and female flowering, plant height and insertion of ear; foliar diseases and insect attack level, length, diameter and filled with cob uniformity, kernel weight and performance. The variables were subjected to analysis of variance and Turkey’s test was applied to 95% of probability to determine the statistical difference between treatment means.